1965
DOI: 10.1063/1.1714368
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Resonance Probes

Abstract: In the last few years there have been several experimental results on resonance probes which were poorly explained by existing theories. They are, briefly: the resonant frequency increases (A) as the bias voltage of the probe is biased strongly negative, and (B) as a probe of smaller area is employed. In this paper, the characteristics of the resonance probe are analyzed on the basis of the resultant series impedance of the plasma and the sheath, the former being expressed by an antiresonant circuit and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…There is a body of early theoretical and experimental work related to the phenomenon of rf resonance both above and below the plasma frequency. [11][12][13] The investigation of collisionless resistance associated with resonance phenomena that is thought to arise due to plasma inhomogeneity, may be said to originate with the work of Tonks. 14 However, the problem did not receive further attention until Herlofson,15 trying to account for resonant scattering observed in connection with ionized meteor trails, was the first to introduce the idea of an effective collision frequency associated with density gradients.…”
Section: Introductionmentioning
confidence: 99%
“…There is a body of early theoretical and experimental work related to the phenomenon of rf resonance both above and below the plasma frequency. [11][12][13] The investigation of collisionless resistance associated with resonance phenomena that is thought to arise due to plasma inhomogeneity, may be said to originate with the work of Tonks. 14 However, the problem did not receive further attention until Herlofson,15 trying to account for resonant scattering observed in connection with ionized meteor trails, was the first to introduce the idea of an effective collision frequency associated with density gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Sheath-plasma resonances first discovered by Takayama, Ikegami, and Miyazaki 3 have been mainly studied for negatively biased electrodes in space 4 ' 5 and in laboratory plasmas. 6,7 In this Letter I present the behavior of the sheath-plasma resonance for a positively biased electrode drawing electron saturation current through an ion-depleted sheath. It is observed that the series resonance vanishes while the parallel antiresonance becomes spontaneously unstable.…”
mentioning
confidence: 99%
“…The physical phenomena which RPs exploit have been known since the 1930s [1]. Research performed in the 1960s demonstrated the feasibility of resonance probes and built a theoretical framework for their use [2][3][4][5]. Several different techniques have been developed using resonance probes and have been well characterized [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%